A predictive analytics approach to improve telecom's customer retention - Omari, Asem; Al-Omari, Omaia; Al-Omari, Tariq; Fati, Suliman Mohamed (Frontiers in Artificial Intelligence, 2025)
Customer retention is a critical challenge for telecom companies, and understanding customer churn can significantly improve business strategies. This paper focuses on developing an accurate predictive model to identify potential customer churn using advanced data analysis techniques. By applying machine learning algorithms, our aim is to improve decision-making processes and enable telecom providers to take proactive measures to retain customers. Through this research, we seek to gain deeper insight into customer behavior, ultimately helping telecom companies improve service offerings and reduce churn rates. We developed and evaluated a diverse set of predictive models using a dataset representing customer churn. Our comparative analysis highlights the strengths and weaknesses of various techniques, and among the developed models, the Support Vector Machine (SVM) achieved the highest performance. The main contribution of this study lies in integrating effective data pre-processing, feature selection, and interpretability into churn prediction models, thus addressing the gaps identified in earlier research.